Selenium Biomarkers in Prostate Cancer Cell Lines and Influence of Selenium on Invasive Potential of PC3 Cells - Hendrickx, Wouter; Decock, Julie; Mulholland, Francis; Fairweather-Tait, Susan; Bao, Yong-Ping (Frontiers in Oncology, 2013)
Dietary selenium intake has been linked to reduced cancer risk, however the underlying mechanisms are yet unknown. We question the commonly used practice of applying selenium concentrations found in human blood to in vitro studies and evaluated the utility of biomarkers, eg glutathione peroxidase 1 (GPx1) and theoredoxin reductase 1 (TrxR1), to determine appropriate selenium levels for in vitro work. Furthermore, we investigated the effects of SeMSC on prostate cancer cell migration and invasion. After excluding cytotoxicity, we demonstrated that prostate cancer cell lines respond differently to selenium treatment as observed through biomarker assessment. We found that the maximum levels of GPx1 activity and TrxR1 expression were reached at lower selenium concentrations in LNCaP compared to PC3 cells, and PC3 compared to DU145 cells. Therefore we discourage the use of selenium concentrations extrapolated from human studies for in vitro work but suggest using a read-out of selenium repletion such as selenium responsive biomarkers. No effect on PC3 migration or invasion was observed after long term SeMSC treatment; however a slight increase was found when treatment was solely administered during the assay. The opposite could be observed when cells were cultured under low serum conditions, with a significant increase in migration upon long term but not upon acute SeMSC treatment. To conclude, these findings indicate that it is imperative to study the selenium sensitivity of an in vitro model preferably using biomarkers before investigating any effects on biological processes, or before comparing models.